PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus pada Karyawan Hotel Patra Jasa Jakarta) - Monica Marsella; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2016)
Labor or human resources have an important role in the company in order to achieve success.Therefore, companies must consider the factors that may affect the performance of employees, such ascompensation and working environment. Achievement of employee performance Patra Jasa Jakarta said notoptimal in which the employee's performance increased in 2012 but decreased performance in 2013. The aim ofthis study was to determine how the compensation, working conditions, and the performance of employees inPatra Jasa Jakarta, as well as to determine the effect of compensation and work environment either partially orsimultaneously on the performance of employees in Patra Jasa Jakarta. This type of research is "explanatoryresearch". The sampling technique used is nonprobability sampling with saturated sampling method that usesall members of the population that all employees (non-led) 120 people. In proving the hypothesis test was usedcorrelation analysis, coefficient determination test, regression test (simple and multiple), and a significance test(t test and F test) with SPSS 16.0. The survey results revealed that the variable compensation (X1) and theWorking Environment variable (X2) partially and simultaneously positive and significant impact on employeeperformance variable (Y). Partially and simultaneously, variable compensation (X1) provide a strongerinfluence on employee performance variable (Y) than the Working Environment variable (X2). Suggestions canbe submitted is the company can evaluate and improve the elements that can affect the performance ofemployees, such as compensation and working environment where opportunities are promoted. and conditionsof hygiene and neatness in the space / workplace still considered good by the employees. The company can alsoprovide regular training and guiding employees so that the level of errors made in the work can be minimizedas possible.